Antimicrobial alkaloids isolated from marine sponges - Minireview - Qaralleh, Haitham; Idid, Syed Zahir; Saad, Shahbudin; Susanti , Deny; Althanubat, Osama; Majali, Ibrahim (Journal of Basic and Applied Research, 2016)
Marine natural products have attracted the attention of scientists to isolate novel biologically active metabolites. Several promising metabolites were discovered from marine sponges with different biological activities including antimicrobial and anticancer. By far, more than 36% of the metabolites discovered from marine organisms were isolated from sponges. In this study, the alkaloids isolated from marine sponges with antimicrobial activity were described.